Engaging head and heart in disciplinary learning: Insights from a threshold concepts-infused university programme - Goebel, Jessica; Maistry, Suriamurthee (Critical Studies in Teaching and Learning, 2023)
Deeper understanding of the factors that influence the course of disciplinary learning could help educators  to  facilitate  the  process  more  effectively.  The  Threshold  Concepts  Framework  (TCF) encompasses cognitive, affective, and contextual aspects of learning, but has not fully examined the dynamics of the process. We explored students’ experiences in a TCF-aligned, cooperative learning programme in economics at a South African university. Through Interactive Qualitative Analysis, data was generated throughfocus groups, interviews,and written reflections. From the detailed descriptions of their learning, rendered in students’ voices, we abstract a representation of  disciplinary  learning  as  a  challenging  and  transformative  process,  requiring  that  students engage with both head (cognition and metacognition) and heart (conation, affect,and identity). If the discipline as experienced aligns with students’ sense of self, learning is more likely to be meaningful, facilitating the engagement of their inner resources to sustain academic commitment and enhance cognitive and metacognitive development.